The New Basel Capital Accord : The Devil Is in the (Calibration) Details - Kupiec, Paul (IMF Working Papers; Working Paper ;, 2001)
This paper considers characteristics of the capital requirements proposed in The New Basel Capital Accord (2001). Formal analysis identifies calibration features that could give rise to unintended consequences that may include: concentration of credit risk in institutions that are less well equipped to measure and manage risks; an overabundance of thinly capitalized high quality long-maturity credits in foundation Internal Ratings-Based (IRB) banks; distortions in the secondary market for discount or premium credits; an increase in the difficulty of resolving distressed financial institutions; and incentives to distort the accuracy of loan loss provisions.